119 구급대원의 직무스트레스와 직무만족도 - 이성희(Sung Hee Lee); 최연희(Yeon Hee Choi) (지역사회간호학회지, 2006)
Purpose: This study was to measure the degree of job stress and job satisfaction and the relationship between job stress and job satisfaction of 119 relief squads. Methods: The subjects were 170 members of 119 relief squads in the Fire Department of D City, and data were collected from 1 April to 20 April, 2006 through a survey using a questionnaire composed of questions on general characteristics (11 items), job stress (6 items) and job satisfaction (20 items). Collected data were analyzed through frequency, percentage, t-test, ANOVA and Pearson's correlation using the SPSS program. Results: The average item score for job stress was 2.77. Role sharing with peers was highest as 3.05. There were significant differences in the degree of job stress according to religion, working period and applying motive. The average item score for job satisfaction was 2.93. Group conflict was highest as 3.18. There were significant difference in the degree of job satisfaction according to religion, working period and applying motive. There were significant differences in the negative correlation between role-sharing with peers among the job stress factors and decision-making factor (r=.53), group conflict factor (r=.58), role implementation factor (r=.63) and personal social-culture factor (r=.53) among the job satisfaction factors. Also, there were significant differences in the negative correlation between co-workers among the job stress factors and decision-making factor (r=.607), group conflict factor (r=.51) and personal social-culture factor (r=.45) among the job satisfaction factors. Conclusion: It is important to develop various methods of job stress management to increase job satisfaction in 119 relief squads.